Luther. Season 1 [videorecording (DVD)] - Kirk, Brian, 1968-; Miller, Sam, 1962 September 28-; Schwartz, Stefan, 1963-; Elba, Idris; Wilson, Ruth, 1982- (Distributed by BBC Worldwide Americas, Inc. ; Distributed in the USA and Canada by Warner Home Video, 2010)
A self-destructive near-genius, Luther might just be as dangerous as the depraved criminals he hunts. Luther follows his own moral code as much as the rules of criminal law. But he quickly becomes locked in a lethal battle of wits with Alicea, a beautiful, highly intelligent mass murderer, and his decision-making process becomes increasingly murky. Luther's lonely path pulls him towards the very edge of temptation. A second series was produced in 2010-11.